2013
DOI: 10.1345/aph.1r540
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, Safety, and Medication Errors Associated with the Use of Inhaled Epoprostenol for Adults with Acute Respiratory Distress Syndrome: A Pilot Study

Abstract: Based on study findings, inhaled epoprostenol may improve oxygenation in patients with ARDS, with findings suggesting a 62.5% response to therapy. The significance of these effects on improving survival remains unknown. The frequency of medication errors observed in this study poses a significant concern regarding the administration of epoprostenol. Further controlled prospective studies are needed to determine the role of inhaled epoprostenol in improving survival in patients with ARDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 24 publications
1
54
2
Order By: Relevance
“…43 Furthermore, some of the cohort studies specifi cally excluded patients whose oxygenation did not respond to therapy, and although averaged measures of oxygenation were found to improve for the group overall, multiple studies report that a signifi cant percentage of patients were nonresponders. [34][35][36]39,44 So, it is possible that inhaled prostaglandins confer no oxygenation benefi t, and these results refl ect improved oxygenation secondary to a change in F io 2 or other concomitant therapies that were not reported (eg, prone positioning, positive end-expiratory pressure setting).…”
Section: Discussionmentioning
confidence: 99%
“…43 Furthermore, some of the cohort studies specifi cally excluded patients whose oxygenation did not respond to therapy, and although averaged measures of oxygenation were found to improve for the group overall, multiple studies report that a signifi cant percentage of patients were nonresponders. [34][35][36]39,44 So, it is possible that inhaled prostaglandins confer no oxygenation benefi t, and these results refl ect improved oxygenation secondary to a change in F io 2 or other concomitant therapies that were not reported (eg, prone positioning, positive end-expiratory pressure setting).…”
Section: Discussionmentioning
confidence: 99%
“…However, observational studies and case series have shown efficacy of inhaled prostaglandins for improved oxygenation in severe hypoxemia due to ARDS. A recent retrospective chart review, which included 16 patients treated with inhaled epoprostenol, showed that epoprostenol improved oxygenation (defined as an improvement in P aO2 /F IO2 of >10% from the baseline) in 62.5% of the treated patients [19, 20]. Therefore, inhaled prostaglandins have been increasingly used lately as a rescue therapy for severe refractory hypoxemia in severe ARDS given its cost effectiveness compared to inhaled nitric oxide as well as similar efficacy for improving oxygenation and safety outcomes [21].…”
Section: Discussionmentioning
confidence: 99%
“…This strategy is advantageous as it facilitates more‐rapid dose titration and does not require preparation of multiple dilutions of epoprostenol. However, a weight‐based approach necessitates multiple dosing calculations, in which errors have been reported . As such, dosing charts have been developed and are recommended to guide calculations and minimize the risk of medication errors …”
Section: Dosing and Administration Of Inhaled Pulmonary Vasodilatorsmentioning
confidence: 99%
“…However, a weightbased approach necessitates multiple dosing calculations, in which errors have been reported. 50 As such, dosing charts have been developed and are recommended to guide calculations and minimize the risk of medication errors. 29 Previously, Flolan (reconstituted with glycine diluent) was the only epoprostenol product available.…”
Section: Inhaled Prostacyclin Analogsmentioning
confidence: 99%